The Role of Positive Religious Coping as a Moderator on the Effect of Perceived Stress and Symptoms of Depression: A Study on Indonesian Students Quarantined at Home during the COVID-19 Pandemic - Nugraha, Dwi Yan; Daud, Muh.; Siswanti, Dian Novita; Zhalifunnas, Muhammad Shafwan (Universitas Muhammadiyah Surakarta, 2022)
Students have faced widespread changes and challenges as a result of the coronavirus disease 2019 (COVID-19) pandemic. How students cope with these disorders is important in determining the ongoing impact of the pandemic on mental health and well-being. This research consists of two studies, namely correlation and experiment. In the correlation study, the researcher wanted to investigate the role of positive religious coping as a mediator on the effect of perceived stress on depressive symptoms among Indonesian students, using the hierarchical regression analysis method. A total of 341 samples in this study were obtained by convenience sampling technique, which focused on students who were infected with the COVID-19 virus, and were or had been quarantined at home for 14 days. Respondents completed online self-report measurements. The results of the analysis show that positive religious coping acts as a mediator on the effect of perceived stress on depressive symptoms among students (β = -0.061; p = 0.029). In an experimental study, researchers wanted to see the role of positive religious coping training in reducing stress and symptoms of depression, which was tested by repeated measure ANOVA. This study uses a nonrandomized pretest posttest control group design. A total of 60 respondents (30 experiments and 30 controls) in this study were recruited using purposive sampling technique. The results of data analysis showed that positive religious coping training was effective in reducing stress (F(2;58) = 28.1; p < .05; η²p = .492), and depression (F(2;58) = 14.9; p < .05; η²p = .340), for students who are undergoing quarantine due to the COVID-19 pandemic. The implications and limitations have been discussed.